2008
DOI: 10.1007/s11099-008-0007-y
|View full text |Cite
|
Sign up to set email alerts
|

Photosystem 2 photochemistry and pigment composition of a yellow mutant of rice (Oryza sativa L.) under different irradiances

Abstract: A yellow leaf colouration mutant (named ycm) generated from rice T-DNA insertion lines was identified with less grana lamellae and low thylakoid membrane protein contents. At weak irradiance [50 μmol(photon) m -2 s -1 ], chlorophyll (Chl) contents of ycm were ≈20 % of those of WT and Chl a/b ratios were 3-fold that of wild type (WT). The leaf of ycm showed lower values in the actual photosystem 2 (PS2) efficiency (Φ PS2 ), photochemical quenching (q P ), and the efficiency of excitation capture by open PS2 cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…It was evident from the decrease of the proportion of light energy used for photochemistry and the increase of the proportion of excess light energy under the LL condition. Our results corroborated the conclusions of earlier investigations (Krause 1988, Chow et al1990, Lee et al 1999, Souza et al 2004, Chen and Cheng 2007, Chen et al 2008.…”
Section: Parameterssupporting
confidence: 93%
“…It was evident from the decrease of the proportion of light energy used for photochemistry and the increase of the proportion of excess light energy under the LL condition. Our results corroborated the conclusions of earlier investigations (Krause 1988, Chow et al1990, Lee et al 1999, Souza et al 2004, Chen and Cheng 2007, Chen et al 2008.…”
Section: Parameterssupporting
confidence: 93%
“…A Chl-deficient rice mutant showed a lower photon absorption rate, and a stronger xanthophyll cycle capacity and a lower degree of photoinhibition (Dai et al 2003). On the other hand, some Chl-deficient rice mutants displayed a higher degree of photoinhibition, either having lower abilities of thermo-dissipation and antioxidative protection (Goh et al 2009) or a higher level of de-epoxidation states of xanthophylls (Chen et al 2008). The results of the present study indicated that, although vegetables used in this study are of either temperate or tropical origin and include C 3 and C 4 plants, 4 yellow-green cultivars showed the same tendency on changes in energy dissipation and photoinhibition (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that several Chl mutants could change their efficiency of energy dissipation and antioxidative protection in order to adapt to high irradiance , Štroch et al 2004, Chen et al 2008, Goh et al 2009). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a scanning electron microscope (S-3400N, Hitachi, Japan) to observe the arrangement trichomes on our C. korshinskii leaf samples. According to methods outlined by Chen et al (2008), leaf samples (5 mm 9 5 mm) were fixed in 4% glutaraldehyde at 4°C for over 6 h, and then washed three times with 0.1 M phosphate buffer solution for 10 min. The samples were then transferred into 1% osmic acid at 4°C for 2 h and washed three times with 0.1 M phosphate buffer solution for 10 min.…”
Section: Scanning Electron Microscopymentioning
confidence: 99%